Targeting the CD27-CD70 Pathway to Improve Outcomes in Both Checkpoint Immunotherapy and Allogeneic Hematopoietic Cell Transplantation - Lutfi, Forat; Wu, Long; Sunshine, Sarah; Cao, Xuefang (Frontiers in Immunology, 2021)
Immune checkpoint inhibitor therapies and allogeneic hematopoietic cell transplant (alloHCT) represent two distinct modalities that offer a chance for long-term cure in a diverse array of malignancies and have experienced many breakthroughs in recent years. Herein, we review the CD27-CD70 co-stimulatory pathway and its therapeutic potential in 1) combination with checkpoint inhibitor and other immune therapies and 2) its potential ability to serve as a novel approach in graft-versus-host disease (GVHD) prevention. We further review recent advances in the understanding of GVHD as a complex immune phenomenon between donor and host immune systems, particularly in the early stages with mixed chimerism, and potential novel therapeutic approaches to prevent the development of GVHD.